Local perceptions of forest, conservation and logging in Papua New Guinea - Paul Sillitoe (Revue d'ethnoécologie)
The future of Papua New Guinea's (PNG) extensive forests is of some concern. Local communities may readily sell logging rights to timber companies to fund elusive ‘development’. Alternatively, they may hold the key to forest conservation. It may be possible, if landowners have some notion of managing forest resources, to build on these practices. But according to some commentators they traditionally lack a conservation ethic. In order to advise on forest policy, it is necessary to try and gauge the practices, attitudes and ideas of local people. This accords with current participatory development approaches to consult ‘grassroots’ opinion, as in indigenous knowledge (IK) research, which aims to facilitate interventions by promoting partnership and an awareness of local perspectives. It is indisputable that local people will be well qualified to define problems, and will be ‘experts’ on their forests. The difficulties encountered in formulating generalisations applicable on a large scale present a barrier to IK informing policy, as in the management of logging and promotion of forest conservation. The short-termism of development, politically driven for immediate returns, presents further problems. We need to evolve methods and formulate principles that will allow some reliable local inputs into policy debates. One way to assess local knowledge and aspirations quickly on a nation-wide level is to use surveys. This paper will discuss a rural community survey conducted in PNG to ascertain peoples’ attitudes to forestry, logging and conservation, and inform policy debates. But a survey is a relatively blunt instrument for assessing the subtleties of IK, having well rehearsed drawbacks. It also glosses over contentious political issues. But what more effective way is there of assessing understanding and ideas widely at the grass-roots in a short time frame?